PENINGKATAN PENDAPATAN UKM MELALUI PENGUASAAN TEKNOLOGI PAKAN LELE DAN PEMANFAATAN LIMBAH LOKAL DESA JATISARI KECAMATAN JATISRONO, KABUPATEN WONOGIRI - widayanti, rochmi (Universitas Muhammadiyah Surakarta, 2017)
IbM activities carried out in the village Jatisari, local village government has formed groups of fish farmers, but due to constraints in the high feed costs, the number of farmers began to decrease from 20 to less than 5 people catfish farmers. Constraints, high feed costs caused by dependence on the feed manufacturers and fish farmers group is limited knowledge about the creation of alternative feed. Limitations in managing the business also experienced group of fish farmers, especially in production planning and financial of the business, through the program IbM, expected these problems can be finished.The IbM program consist of:(1)business management training (business plan), (2) training of feed manufacturing catfish with the use of local waste and can be as alternative feed, (3) training on mastery of engine technology prill fish pellets simple and integrated with dryers that can be used as an alternative to the rainy season. Outcomes of this program can be formed business group catfish farmers are independent, able to manage the business properly, can make alternative feed and capable of implementing the technology.Â